Dolines Phenomenon Determination Using by Geological and Geoelectrical Resistivity Survey Approach in Bedoyo Village, Ponjong Subdistrict, Gunung Kidul Regency - Fatimah Fatimah; alhussein flower rizqi (Jurnal Geosains dan Teknologi, 2022)
Gunung Kidul Regency is a highland consisting of carbonate rocks dominantly. Bedoyo village in Ponjong sub district has a lot of dolines, but in the summer season, the dolines become dry and could not be water storage. Geological mapping is included in geomorphological, rock observation, structural mapping also petrographical analysis in the laboratory. A Geophysics survey is to observe the subsurface rock distribution laterally and vertically with dipole-dipole configuration. The resistivity method is to determine the resistivity value for the depth of fewer than 40 meters with the length of electrodes of about 250 meters. The result of the geological and geophysical analysis is to review the dolines phenomenon that could not be a shallow aquifer. It is caused by the subsurface condition beneath the dolines consisting of carbonated rocks with poor porosity, lenses of impermeable tuffaceous claystone, and igneous rock. Those rock basements have a moderate to poor porosity in the aquifer. The less opportunity to be a good aquifer if the deeper rock is an impermeable igneous rock. An alternative geophysical survey is needed to observe the deeper rock vertically.